2015
DOI: 10.1182/blood-2014-03-561019
|View full text |Cite
|
Sign up to set email alerts
|

Cytoadhesion of Plasmodium falciparum–infected erythrocytes to chondroitin-4-sulfate is cooperative and shear enhanced

Abstract: Key Points• Cytoadhesion of parasitized erythrocytes depends on the intermolecular distance between neighboring chondroitin-4-sulfate molecules.• VAR2CSA is an allosteric adhesin that binds chondroitin-4-sulfate in a cooperative and shear stress-induced manner.Infections with the human malaria parasite Plasmodium falciparum during pregnancy can lead to severe complications for both mother and child, resulting from the cytoadhesion of parasitized erythrocytes in the intervillous space of the placenta. Cytoadher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 54 publications
1
48
0
1
Order By: Relevance
“…A similar value has indeed been reported for the PfEMP-1/CSA-bond (71). The knob density is taken to be 10/mm 2 following earlier measurements for the same strain (19). This indicates that both receptor and ligand densities might be limiting.…”
Section: Estimating Schizont Parameters From Flow Datasupporting
confidence: 63%
See 3 more Smart Citations
“…A similar value has indeed been reported for the PfEMP-1/CSA-bond (71). The knob density is taken to be 10/mm 2 following earlier measurements for the same strain (19). This indicates that both receptor and ligand densities might be limiting.…”
Section: Estimating Schizont Parameters From Flow Datasupporting
confidence: 63%
“…Early measurements reported that their density increases from $20 to 60/mm 2 from trophozoite to schizont (15), but these numbers are very variable and differ considerably between different malaria strains. For the strain used here, the knob density increases from $9 to 15/mm 2 from trophozoite to schizont (19). With a RBC surface area of A ¼ 136 mm 2 that is approximately constant over the developmental cycle (11), this corresponds to an increase of the numbers of knobs from N k z 1000-2000.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…1 M alaria is a prehistoric disease caused by Plasmodium, a genus of parasitic protozoans. Mentioned in the ancient Chinese, Greek, Sanskrit, and Roman literature, the Italian word "mal'aria" for "bad air" refers to an infection that has profoundly influenced the history of human civilization.…”
mentioning
confidence: 99%